Meta-Analisis Model Project Based Learning terhadap Kemampuan Pemecahan Masalah dalam Pembelajaran Matematika - Yestina, Ratna; Ratnaningsih, Nani; Ni'mah, Khomsatun (FONDATIA, 2024)
This research aims to analyze the effect size of using the Project-Based Learning (PjBL) model on problem-solving abilities in mathematics learning and investigate the effect size based on educational levels. The research method employed is quantitative with meta-analysis, aiming to summarize, evaluate, and integrate the results of several published studies. Data collection techniques involve documentary studies by searching national and international journals published between 2015 and 2023. A total of 24 studies met the predetermined inclusion and exclusion criteria, and the effect sizes of each study were calculated. Subsequently, the overall average effect size and effect sizes based on educational levels were calculated. Data analysis was conducted using JASP software version 0.18.1.0. The results of this research indicate that the effect size of the Project-Based Learning model on problem-solving abilities in mathematics learning is significantly large, with an effect size of 0.973. Furthermore, statistically significant differences were reported in the effect sizes of the PjBL model on problem-solving abilities in mathematics learning across educational levels. The implementation of the PjBL model has a very large effect size on problem-solving abilities in mathematics learning for elementary, and college-level students. Meanwhile, at junior high school and the senior high school level, the PjBL model on problem-solving abilities in mathematics learning has a large and amoderate effect size.